Sectoral analysis of ESG (environmental, social, and governance) integration in corporate governance: insights from sustainable finance - Andi Primafira Bumandava Eka; PA Andiena Nindya Putri; Rita Zulbetti; Loso Judijanto; Klemens Mere (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This research explores the critical intersection of sustainable finance and corporate governance, emphasizing the role of Environmental, Social, and Governance (ESG) factors across various industry sectors. The primary objective is to highlight how ESG considerations impact long-term value creation and risk mitigation within sectors such as technology, semiconductors, building, commercial services, and healthcare. Through a comparative analysis of ESG scores, the study aims to uncover patterns and discrepancies in ESG integration across these sectors, providing insights into their respective commitments to sustainability. To address the reviewer's feedback, the study clearly articulates its research goal: to assess how different sectors perform regarding ESG metrics and identify the factors contributing to observed variations. The methodology includes the collection of secondary ESG data from reputable sources, such as the Dow Jones Sustainability Index, using statistical analysis to identify trends and differences in ESG adherence. The findings reveal significant sector-specific variations, with technology and semiconductor sectors achieving the highest ESG scores, while the building and healthcare sectors exhibit substantial room for improvement. The implications of these results are practical; businesses can leverage these insights to enhance their ESG integration strategies. In conclusion, the study advocates for a stronger incorporation of ESG metrics into corporate decision-making processes, promoting a future of sustainable and ethical business practices across industries. By doing so, it aims to foster long-term resilience and positive societal impact.